Convenient protocols for Mizoroki–Heck reactions of aromatic bromides and polybromides with fluorous alkenes of the formula H2CCH(CF2)n−1CF3 (n = 8, 10). Issue 42 (6th October 2016) - Su, Haw-Lih; Balogh, Janos; Al-Hashimi, Mohammed; Seapy, Dave G.; Bazzi, Hassan S.; Gladysz, John A.
Abstract : Under "Jeffrey conditions" involving large amounts of ammonium salts, the title reactions can be carried out in high yields; the resulting CC linkages are easily hydrogenated. Abstract : The fluorous alkenes H2 CCHRf n (Rf n = (CF2 ) n −1 CF3 ; n = 8, 10) undergo the Mizoroki–Heck reaction with a variety of aromatic monobromides and polybromides such as 1, 3- and 1, 4-C6 H4 Br2, 1, 3, 5-C6 H3 Br3, 1, 3, 5-C6 H3 Br2 Cl, 1, 4-XC6 H4 Br (X = CF3, Rf8, COCH3, CN, 1, 4-OC6 H4 Br), 1, 2-O2 NC6 H4 Br, 5-bromoisoquinoline, 5-bromopyrimidine, 3-bromo-5-methoxypyridine, and 3, 5-dibromopyridine (sixteen examples, 78% average isolated yield). Typically, 1.2–2.4 equiv. of alkene are employed per Ar–Br bond, together with Pd(OAc)2 catalyst (4–5 mol%/Ar–Br bond), n -Bu4 N + Br − (0.8–1.0 equiv./Ar–Br bond), NaOAc (1.2–2.4 equiv./Ar–Br bond), and 3 : 1 w/w DMF/THF as solvent (120 °C). No effort is necessary to exclude air or moisture, and reactions may be conducted on >10 g scales. Only E isomers of the products Ar(CHCHRf n ) m are detected. Thirteen representative examples are hydrogenated (Pd/C, balloon pressure H2 ), giving Ar(CH2 CH2 Rf n ) m (92% average isolated yield).